Challenges of Integrating Disaster Risk Management and Climate Change Adaptation Policies at the National Level: Bangladesh as a case (Global Journal of Human-Social Science, 2013)
Disaster management and climate change adaptation emerges as the greatest long term threats that are challenging overall development efforts of Bangladesh. Government of Bangladesh is playing a central role for disaster management and climate change adaptation. The Ministry of Food and Disaster Management (Mo FDM) and the Ministry of Environment and Forestry (Mo EF) are the two key ministries responsible for developing and implementing various programs and policies for disaster management and climate change adaptation respectively. This paper discusses the challenges for linking disaster management and climate change adaptation in Bangladesh. Structural arrangements, policy development process, funding arrangement of the Mo FDM and Mo EF have analysed to understand the challenges for integration.
Keywords: disaster risk reduction; climate change; disaster management; adaptation; sustainable develop-ment; Bangladesh